The benefits of considering gender in economic development - Sujata Ganguly; Elena Nikolova (Global Labor Organization (GLO), 2024)
This chapter argues that gender equality and economic development are tightly intertwined, and that gender aspects should be an essential consideration for economic development. The chapter starts by developing a conceptual framework explaining how gender equality and economic development influence each other. In particular, the framework emphasizes the interaction between SDG 5 (gender equality), SDG 3 (good health and well-being) and SDG 4 (quality education). It then applies the developed framework to discuss how gender affects economic development in four broad domains with reference to the green economy. First, the chapter discusses the links between gender and economic development in employment and social protection, followed by unpaid work and the care economy. Second, the chapter discusses how we can bridge the gap between the green economy and gender inequality. Finally, the chapter points out that the post-COVID-19 recovery can be exploited as a window of opportunity to initiate a development model that encompasses gender inclusiveness and the green economy. The chapter concludes with recommendations for gender-sensitive programmes and policies that can be used by governments to fast-track economic development and growth, and to build inclusive and resilient societies.
Keywords: J16; O12; O13; 330; Green economy; Gender equality; Economic development; Employment; Social protection; Unpaid work; Care economy; COVID-19